Language Production Of Children Aged 6 Years Old: A Psycholinguistics Study - Murni Mahmud; Muftihaturrahmah Burhamzah; Rizal Alamza Amal; Abdul Halim (Seminar Nasional LP2M UNM, 2022)
Abstrak. This study is about the language production ability of children aged 6 years old. This is a psycholinguistics study which aims to investigate the language production of the children aged 6 years old. This study was conducted at the Institute of Play International School Makassar. The method used in this research is qualitative descriptive method and psycholinguistics approach. This research investigated four children intensively by analyzing the utterances produced by the children based on syntactic and phonological analysis. The results of the study show that children have language ability on par with adolescents in general in producing sentence and utterances, and sometimes have difficulty in understanding the meaning of sentences spoken by other interlocutors. Overall. language ability of the children developed normally. They able to use their language to communicate with people around them and therefore, they didn’t have difficulty to use conversational skills in communication.